The influence of medical-demographic and socio-economic factors on the detection of occupational morbidity in agricultural workers - G. A. Bezrukova; T. A. Novikova (Сибирский научный медицинский журнал, 2024)
According to the expert community, the level of occupational morbidity (OM) registered in Russia in a number of sectors of the economy is underestimated, and is determined not only by working conditions, but also by the medical, demographic and socio-economic living factors of the working population. Aim of the study was to identify priority medical, demographic and socio-economic factors affecting the detection of OM in agricultural workers (AW). Material and methods. The information base of the study was the competent materials of Saratovstat and the Department of Rospotrebnadzor in the Saratov region. The dynamics of the factorial indicators of the life activity of the AW was evaluated by the time series method, their relationship with the level of OM – using multiple correlation and regression analysis. Results and discussions. From 2009 to 2019 levels detected in the region of OM agricultural workers decreased in 3.2 times with 5.0 to 1.56 per 10,000 employees in the agricultural sector. According to the results of the analysis of 4 multiple regression models describing the influence of medical-demographic and socio-economic factors on the detection of OM AW, three priority indicators were identified among 12 regressors – the number of people employed in the “Agriculture, hunting, forestry” industry (r1 = 0.854), the number of advisory and expert visits of specialists of the center of occupational pathology to the districts of the region (r10 = 0.884) and mortality in working age (r12 = 0.742). Formed on the basis of these independent variables, the generalized model “OM (Y) – factorial signs of the medical and demographic situation” showed statistical reliability and determined 86.4 % of the variability of the OM detected in AW with a high closeness of the relationship (R = 0. 9296) between the level of OM and the set of regressors. Conclusions. The established medical and demographic factors that statistically significantly affect the detection of occupational morbidity of agricultural workers must be taken into account in the sanitary and hygienic monitoring of occupational pathology of the working rural population.